The ideal character of the general will and popular sovereignty in kant - Marey, Macarena (2018)
In this paper, I examine Kant's reception of and solution to the problem of the unity of the political will. I propose that Kant distances himself from the modern paradigmatic foundations of sovereignty principally with his theses of the ideality of the general will (section II) and of the apriority of the justification of popular sovereignty (section III). My interpretative hypothesis is that Kant solves the problem by grounding sovereignty in a conceptual element which is new in the history of political philosophy, i. e. the a priori unified omnilateral will. In section IV, I explain why my reading of the ideality of the general will can respond to seemingly plausible objections arising from Kant's own texts and how it works in the face of concrete political states of affairs.